2016
DOI: 10.3390/polym8050159
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Mechanism of Metal-Mediated Polymerization of Phenolic Resins

Abstract: Phenol-formaldehyde (PF) resin is a high performance adhesive, but has not been widely developed due to its slow curing rate and high curing temperature. To accelerate the curing rate and to lower the curing temperature of PF resin, four types of metal-mediated catalysts were employed in the synthesis of PF resin; namely, barium hydroxide (Ba(OH) 2 ), sodium carbonate (Na 2 CO 3 ), lithium hydroxide (LiOH), and zinc acetate ((CH 3 COO) 2 Zn). The cure-acceleration effects of these catalysts on the properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 26 publications
3
52
0
Order By: Relevance
“…Table shows the thermal properties of the pure PF, HOPF, and cure‐accelerated HOPF resins. Compared with the pure PF resin, the HOPF resin exhibited similar thermal stability, which was consistent with previous work . While HOPF resin exhibited a higher weight residue at 600 °C than the pure PF resin, indicating that the HOPF resin possessed a tighter network.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Table shows the thermal properties of the pure PF, HOPF, and cure‐accelerated HOPF resins. Compared with the pure PF resin, the HOPF resin exhibited similar thermal stability, which was consistent with previous work . While HOPF resin exhibited a higher weight residue at 600 °C than the pure PF resin, indicating that the HOPF resin possessed a tighter network.…”
Section: Resultssupporting
confidence: 89%
“…As seen, the weak intensity of chemical shift at 155.0–163.0 ppm in the spectrum of HOPF may be caused by the low concentration of phenolic resin in DMSO‐ D6 during the 13 C‐NMR testing, which could also be observed in other report. The unsubstituted para and ortho carbons, which were the main reactive sites for methylolation reactions, could be observed at 119.5–121.4 and 116.0–117.1 ppm, respectively . While the absence of chemical shifts at 119.5–121.4 ppm indicated that all the reactive sites at the para positions were substituted.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Phenolic resin (PR), i. e., phenol formaldehyde resin, is a synthetic polymer prepared by the polycondensation between phenol and formaldehyde . Because PR possesses the capabilities of heat resistance, flame retardancy and electrical insulation, it has been widely applied in electronic industry, aerospace engineering, building materials and electrical engineering .…”
Section: Introductionmentioning
confidence: 99%